Mejoramiento de la calidad de servicio técnico, índices ttik-fmik, utilizando la metodología de las cadenas de markov en el alimentador 1 lasso del sistema de distribución de la Empresa Eléctrica Provincial Cotopaxi S.A. para el año 2014 - Herrera Tapia, Marcela Patricia (2015)
The energy supply in our country is the public service useful with national interest, therefore, It has been created regulations and laws in the electricity sector, to regular and control the energy quality in this country. The entities regulation in Ecuador is ARCONEL, That control, regulate and sanction all companies that not fulfil laws establish in it, within its concession area. The present work has proposal consider options for to improve reliability in a primary feeder type radial in Cotopaxi Province apply Markov chain methodology and technique re-configuration of the grid. To apply these techniques allow us get better index reliability the Interruption Media Frequency for KVA Install (FMIK) and interruption time by KVA install (TTIK), primary feeder 1 part branch Lasso, this belong to Cotopaxi Province Electric Company S.A. by means regulation 004/01 emit by ARCONEL be about index the systems electricity reliability must fulfil with acceptable limit every company distributor such as rural and urban supply....